Penilaian Persepsi Diri Tentang Body Shamming Di Kalangan Mahasiswa Universitas Islam Negeri Sumatera Utara Fakultas Dakwah Dan Komunikasi Jurusan Bimbingan Penyuluhan Islam - Dalimunthe, Hamdal Afgani; Hanafi, T. Rifa; Nur, Muhammad Rifa; Mardiyah, Ainul (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
Body shaming is a behavior that gives a negative assessment of someone's body, which has a serious impact on mental health. This study aims to determine the assessment of Islamic Guidance and Counseling (BPI) students about body shaming and its impacts. Using a qualitative approach with a case study method, this study conducted interviews with four BPI student informants. The results of the study indicate that body shaming has a detrimental effect on an individual's mental and emotional health. This study recommends the importance of increasing awareness of the negative impacts of body shaming.